Programmes of Industrial Development 1956-61 (Electrical Engineering Industries) - Planning Commission (Planning Commission Government of India, 1959)
The document on Programmes of Industrial Development (1956–61) focuses on the growth and strategic planning of India’s electrical engineering industries during the First and Second Five-Year Plans. It highlights achievements in transformers, motors, electric cables, and other electrical products, while addressing production shortfalls in consumer goods such as electric fans, lamps, batteries, and radio receivers. The report outlines ambitious expansion targets for 1960–61, including increased capacities for transformers (1.5 million KVA), motors (600,000 H.P.), and electric cables (334 million yards), alongside establishment of new manufacturing units in key locations. Challenges such as raw material dependence, quality improvement, and import substitution are discussed, with development councils proposed to guide industry-specific strategies. Emphasis is placed on integrating public and private sector initiatives, promoting domestic self-sufficiency, and positioning India competitively in international markets. The report reflects a systematic approach to industrial growth through capacity augmentation, technological advancement, and strategic planning to support national economic development.
Government of India Planning Commission
Keywords: Electrical Engineering; Industrial Development; Five-Year Plan; Electric Cables; Electric Fans; Electric Lamps; Transformers; Motors; Production Capacity; Raw Materials; Export Promotion; Industrial Strategy